Cluster Preface: Development and Applications of Novel Ligands/Catalysts and Mechanistic Studies on Catalysis - Zhang, Zhipeng; Zhao, Baoguo (Synlett, 2022)
Zhipeng Zhang (left) received his B.S. degree from Shandong University (China) in 2004, and his Ph.D. degree from the Shanghai Institute of Organic Chemistry (SIOC) in 2010 under the supervision of Professor Kuiling Ding. In 2011, he began his postdoctoral studies with Professor Benjamin List at the Max Planck Institute for Coal Research in Mülheim an der Ruhr, Germany. After three years of research on asymmetric organocatalysis, he joined the group of Professor Jin-Quan Yu at The Scripps Research Institute in La Jolla, California as a postdoctoral research associate in 2014. He subsequently worked at the Genomics Institute of the Novartis Research Foundation (GNF) from 2016, before he began his independent career as a professor at the East China University of Science and Technology (ECUST) in 2017. His current research interests include asymmetric catalysis and synthetic methodology, focusing on the design and development of novel chiral ligands and catalysts. Baoguo Zhao (right) received his B.S. degree from Wuhan University in 1996, his M.S. degree from Nanjing University under the supervision of Professor Jianhua Xu in 2002, and his Ph.D. degree from the Shanghai Institute of Organic Chemistry (SIOC) under the supervision of Professor Kuiling Ding in 2006. He subsequently worked with Professor Yian Shi for five years as a postdoctoral fellow at the Department of Chemistry of Colorado State University. In 2011, he joined Shanghai Normal University at the Department of Chemistry as a full professor. His current research interests are in the area of biomimetic asymmetric catalysis, including the development of bioinspired chiral catalysts and synthetic methodologies.
Keywords: ligands; catalysts; transition-metal; organocatalyst; chemoselectivity; regioselectivity; stereoselectivity; enantioselectivity